Idiopathic Thrombocytopenic Purpura Misdiagnosed as Hereditary Angioedema - Michelle Fog Andersen; Anette Bygum (Hindawi Limited, 2015)
Hereditary angioedema is a rare, but potentially life-threatening genetic disorder that results from an autosomal dominant trait. It is characterized by acute, recurrent attacks of severe local edema, most commonly affecting the skin and mucosa. Swelling in hereditary angioedema patients does however not always have to be caused by angioedema but can relate to other concomitant disorders. In this report we are focusing on misdiagnosis in a patient with known hereditary angioedema, whose bleeding episode caused by idiopathic thrombocytopenic purpura was mistaken for an acute attack of hereditary angioedema. The case illustrates how clinicians can have difficulties in handling patients with rare diseases, especially in the emergency care setting.